2020
DOI: 10.1097/brs.0000000000003295
|View full text |Cite
|
Sign up to set email alerts
|

Conservative Versus Operative Treatment of Stable Thoracolumbar Burst Fractures in Neurologically Intact Patients

Abstract: Study Design. Nonrandomized, retrospective, comparative, and single-center trial. Objective. The aim of this study is to compare the long-term clinical and radiographic results of thoracolumbar burst fractures in neurologically intact patients, treated surgically or nonsurgically with the aim to optimize their management. Summary of Background Data. There is an ongoing controversy regarding the treatment of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
30
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 21 publications
2
30
0
2
Order By: Relevance
“…Los resultados clínicos a largo plazo en fracturas tipo estallido (A3 y A4) no parecen tener diferencias clínicamente significativas con ambos tipos de tratamiento, aunque los resultados radiológicos sean mejores en aquellos operados. 27 Asimismo, el tratamiento quirúrgico de estas lesiones se relaciona con una mejoría del dolor a corto plazo y tiempos de retorno a las actividades laborales y de la vida cotidiana más rápidos. 28 En este estudio, un subgrupo de ocho pacientes con un TLICSS <4 fue operado, con su consentimiento y el de su familia quienes optaron por este método para evitar períodos prolongados de inmovilización, reposo y dolor junto con las potenciales consecuencias de estos.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Los resultados clínicos a largo plazo en fracturas tipo estallido (A3 y A4) no parecen tener diferencias clínicamente significativas con ambos tipos de tratamiento, aunque los resultados radiológicos sean mejores en aquellos operados. 27 Asimismo, el tratamiento quirúrgico de estas lesiones se relaciona con una mejoría del dolor a corto plazo y tiempos de retorno a las actividades laborales y de la vida cotidiana más rápidos. 28 En este estudio, un subgrupo de ocho pacientes con un TLICSS <4 fue operado, con su consentimiento y el de su familia quienes optaron por este método para evitar períodos prolongados de inmovilización, reposo y dolor junto con las potenciales consecuencias de estos.…”
Section: Discussionunclassified
“…Destacamos que la mitad de nuestros pacientes fueron tratados quirúrgicamente a pesar de que el TLICSS resultara <4. Este es un punto controversial, porque la evidencia disponible 27 no es concluyente sobre el patrón de referencia terapéutico para las fracturas tipo estallido sin compromiso neurológico.…”
Section: Discussionunclassified
“…At present, most scholars at home and abroad believe that even if there is no symptom of the spinal cord or nerve compression, surgical treatment is still advocated [6]. The purpose of surgical treatment is to restore the stability of the spine and to decompress the nerve structure in patients with progressive aggravation of the spinal cord or nerve compression symptoms [7]. Some studies have shown that the bone fragments protruding into the spinal canal can be absorbed by themselves, and if the spine is kept in order, there will be no secondary spinal stenosis in the later stage.…”
Section: Introductionmentioning
confidence: 99%
“…It is commonly accepted that considering the presence of unstable and definitive discoligamentous injuries in types B and C, performing an arthrodesis is logical in these cases [4]. However, for type A fractures which are the most common, there is no therapeutic consensus, and treatment varies according to the authors, ranging from conservative treatment with a cast to a surgical procedure with a vertebroplasty, using an open or a percutaneous fixation, and sometimes a corporectomy and a fusion are performed [5,6].…”
Section: Introductionmentioning
confidence: 99%